Prenatal Diagnosis Leads to Early Diagnosis of Transfusion-Dependent Thalassemia and Better Growth Outcomes - Natthida Asawasudsakorn MD; Supanun Lauhasurayotin MD; Hansamon Poparn MD; Kanhatai Chiengthong MD; Darintr Sosothikul MD; Noppadol Chaiyasit MD; Piti Techavichit MD (SAGE Publishing, 2021)
Thalassemia is the most common hematological transfusion-dependent disease in Thailand. Even though prenatal diagnosis (PND) can detect the condition, many new cases are diagnosed in pediatric practice. This study assessed the clinical outcome of patients with thalassemia who did PND. One hundred and six participants (53 female, 50%), with a median age of 8.5 years (Interquartile range [IQR] 8.00), were enrolled in the study. Twenty-one participants (19.8%) were prenatally diagnosed with thalassemia, with a median age of 8 years (IQR 9.00), 16 were diagnosed with transfusion-dependence thalassemia (TDT), and 5 participants were diagnosed with non-TDT. Another 80.2% did not prenatally diagnose, with a median age of 9 years (IQR 8.00). The PND group found early diagnosis compared with a non-PND group, at a median age of 6 months versus 15 months. There was a significant early diagnosis ( P  < .001). Furthermore, the participants' height for age z -score was significantly superior in the PND group ( P  = .018). Even though the result of PND was abnormal, the parents still willing to continue with the pregnancy. The reason was they wanted to have a child. However, their child may require lifelong transfusion therapy.